Introgression of stem rust resistance gene Sr36 into durum wheat back ground using marker assisted backcross breeding - Sai Prasad, SV; Singh, Sushil Kumar; Vinod, Vinod; Ambati, Divya; TL, Prakasha; Singh, Jang Bahadur; Dubey, Vijay Gajanan; Kantwa, SR; Mishra, Akhilesh Nandan (Journal of Cereal Research, 2014)
India is one of the major producers of durum wheat in the world. Rusts are the important diseases which are considered to be most important constraints in the global wheat production. Stem rust caused by Puccinia graminis sf. sp. tritici has been particularly severe on durum wheat. Even though the durum wheat offers resistance against certain aggressive and more virulent pathotypes of 40 group like 40A (62G29) and 40-1 (62G29-1), it is highly susceptible to certain other pathotypes belonging to 117 group. Wheat stem rust resistance gene Sr36 (syn. SrTt-1), derived from Triticum timopheevii shows effectiveness to many stem rust pathotypes including 117-6 (37G19) which is highly virulent to durum wheat. Presently, Sr36 gene is present in bread wheat background, whereas, none of the durum wheat genotypes found to have Sr36 gene. An effort is being made to transfer Sr36 gene into most popular durum variety HI 8498 by utilizing molecular marker assisted backcross breeding.